MENULIS CERPEN DENGAN MODEL PEMBELAJARAN LEARNING COMMUNITY PADA SISWA KELAS X SMA - Mimi Ansari (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
Writing Short Story with Learning Community Model in Class X Senior High School. This study aimed to describe (1) the influence of Learning Community on students' motivation in writing short stories, and (2) increase the skills to write short stories by Learning Community model. The research method used Classroom Action Research with a procedure using two cycles. Data collection techniques using test and non-test techniques. The data collected was analyzed using quantitative and qualitative techniques. Results of research on class X State Senior High School 1 of Sunggal shows average score of student skills to write short stories in pre-cycle 64,15 and in the first cycle increased to 72,54 but has not yet reached the average value of minimal completeness criteria (75,00) so that the necessary implementation of the action in the second cycle with the results of the average score over the minimal completeness criteria is 78,25. It was concluded that by applying the Learning Community model can improve students 'skills in writing short stories as well as a means to foster students' creativity and ability to collaborate with peers. The application of this learning community model is advised to be applied by the teacher for being able to answer the demands of the curriculum current and future.